2015
DOI: 10.1089/jwh.2014.4961
|View full text |Cite
|
Sign up to set email alerts
|

Missed Opportunities: Screening and Brief Intervention for Risky Alcohol Use in Women's Health Settings

Abstract: Women's health clinics may be an ideal setting to implement SBIRT and future research should address treatment efficacy in these settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Women usually visit their primary care physician for reasons other than their alcohol use. In primary care, unless alcohol screening is systematic, women tend to be missed (Amico, et al, 2005;Hettema et al, 2015;Weisner & Matzger, 2003); however, when screening is conducted systematically with a standardized instrument and a protocol that screens all women rather leaving it up to clinician judgement, there is no longer a difference (Ballesteros et al, 2004). Several screeners for women with alcohol use disorders have evidence of validity.…”
Section: Alcohol Treatment Services For Womenmentioning
confidence: 99%
“…Women usually visit their primary care physician for reasons other than their alcohol use. In primary care, unless alcohol screening is systematic, women tend to be missed (Amico, et al, 2005;Hettema et al, 2015;Weisner & Matzger, 2003); however, when screening is conducted systematically with a standardized instrument and a protocol that screens all women rather leaving it up to clinician judgement, there is no longer a difference (Ballesteros et al, 2004). Several screeners for women with alcohol use disorders have evidence of validity.…”
Section: Alcohol Treatment Services For Womenmentioning
confidence: 99%
“… 18 For example, one study found that one-third of women who endorsed alcohol consumption in women’s health clinics were not asked how much they drank and that a majority of women drinking at risk levels did not receive advice on low-risk limits. 91 Another study concluded that approximately half of women at risk of an AEP did not receive information pertaining to this risk from their health care providers. 91 These findings corroborate national survey data of family planning clinicians, which found that of these clinicians, approximately one-third used a validated screening measure and one-fifth provided a referral that consisted of more than a list of treatment options.…”
Section: Barriers and Facilitators To Sbirt Implementationmentioning
confidence: 99%
“… 91 Another study concluded that approximately half of women at risk of an AEP did not receive information pertaining to this risk from their health care providers. 91 These findings corroborate national survey data of family planning clinicians, which found that of these clinicians, approximately one-third used a validated screening measure and one-fifth provided a referral that consisted of more than a list of treatment options. 92 …”
Section: Barriers and Facilitators To Sbirt Implementationmentioning
confidence: 99%
“…Service providers report being reluctant to ask women about their alcohol use, due to fears of jeopardizing their clinical relationship, or being perceived as judging and shaming women’s behavior [18,19]. While research [20] and prevention efforts such as the Women Want to Know campaign in Australia (fare.org.au) indicate that women appreciate the opportunity to discuss their alcohol use, and learn about ways to improve their health, persistent barriers exist for women to answering questions about alcohol use during pregnancy. For example, women report not feeling safe to report their alcohol use for fear they will be seen negatively by their service provider for their continued use in pregnancy, out of concern about involvement from the child welfare or justice systems, or out of the perception that accessible and helpful outpatient options are unavailable [19,21,22].…”
Section: Introductionmentioning
confidence: 99%